Alopecia areata and overt thyroid diseases: A nationwide population‐based study. Issue 12 (17th September 2018) - Han, Tae Young; Lee, June Hyunkyung; Noh, Tai Kyung; Choi, Min Wha; Yun, Jae‐Seung; Lee, Kyung Ho; Bae, Jung Min
Abstract: An association between alopecia areata (AA) and other autoimmune diseases has been reported. We investigated the associations between AA and overt autoimmune thyroid diseases. A nationwide, population‐based, cross‐sectional study was performed using the Korea National Health Insurance claims database. We defined patients with AA as those whose records showed at least four physician contacts in which AA, alopecia totalis (AT) or alopecia universalis (AU) was the principal diagnosis. We also established an age‐ and sex‐matched control group without AA. In a subgroup analysis, patients with AT or AU were classified into the severe AA group, and the remainder were classified into the mild to moderate AA group. Patients with AA were at an increased risk of Graves' disease (odds ratio [OR], 1.415; 95% confidence interval [CI], 1.317–1.520) and Hashimoto thyroiditis (OR, 1.157; 95% CI, 1.081–1.237), and the associations were stronger in the severe AA group (Graves' disease: OR, 1.714; 95% CI, 1.387–2.118; Hashimoto thyroiditis: OR, 1.398; 95% CI, 1.137–1.719). In conclusion, AA was significantly associated with overt autoimmune thyroid diseases. Furthermore, the risk was much higher in the severe AA group.